The Impacts of FDI Inflows on Carbon Emissions: Economic Development and Regulatory Quality as Moderators - Huang, Yanyan; Chen, Fuzhong; Wei, Huini; Xiang, Jian; Xu, Zhexiao; Akram, Rabia (Frontiers in Energy Research, 2022)
With the accelerated development of the global economy, environmental issues have gradually become prominent, which in turn hinders further high-quality economic development. As one of the important driving engines, cross-border flowing FDI has played a vital role in promoting economic development and caused environmental degradation in most host countries as well. Utilizing panel data over the period of 1996 to 2018 for the G20 economies, the purpose of this study is to investigate the impacts of FDI inflows on carbon emissions, and further explore the influence channels through the moderating effects of economic development and regulatory quality. To produce more robust and accurate results, the approach of the feasible generalized least squares is utilized in this study. Meanwhile, this study also specifies the heteroscedasticity and correlated errors due to the huge differences and serial correlations among the G20 economies. The results indicate that FDI inflows are positively associated with carbon emission, as well as both economic development and regulatory quality negatively contribute to the impacts of FDI inflows on carbon emissions. It implies that although FDI inflows tend to increase the emissions of carbon dioxide, FDI inflows are more likely to mitigate carbon emissions in countries with higher levels of economic development and regulatory quality. Therefore, the findings are informative for policymakers to formulate effective policies to help mitigate carbon emissions and eliminate environmental degradation.